DEVELOPMENT WITHOUT HUMAN DEVELOPMENT - Shaikh, Babar Tasneem (Journal of Ayub Medical College Abbottabad, 2016)
Whilst Pakistan is making significant improvements in macro-economics, infrastructures, industry, roads, information and communication; human development is somewhere somehow seems neglected. Indicators of livelihood, health, education, water & sanitation, nutrition & food security, hence decent livings are lagging far behind. State is showing its seriousness by developing poverty reduction strategies, income support programs, health insurance and other safety nets, yet the course of action calls for a stock taking. There are lot of expectations from the devolved system of local government to re-prioritize the social sector investments as well as expenditures. Women and youth need to be the mainstay to make them part of the overall development process, through proving education, employment and empowerment. All efforts of the government need to be sustained in order to be on track on the roadmap of sustainable development goals.